A fluorine-functionalized microporous In-MOF with high physicochemical stability for light hydrocarbon storage and separation. Issue 10 (22nd August 2018) - Fan, Weidong; Liu, Xiuping; Wang, Xia; Li, Yue; Xing, Chengyong; Wang, Yutong; Guo, Wenyue; Zhang, Liangliang; Sun, Daofeng
Abstract : An ultra-stable fluoro-functional microporous In-MOF with high acetylene and propene/propane adsorption capability and efficient potential for light hydrocarbon separation. Abstract : The storage and separation of hydrocarbons is of great importance for the petrochemical industry. Herein, we report a fluorine-functionalized microporous indium (In) metal–organic framework (UPC-104) for light hydrocarbon storage and separation. UPC-104 can be stable up to 300 °C, and can retain its framework in acidic and alkaline aqueous solutions (pH 1–11). Remarkably, the material exhibits very high H2 (230.8 cm 3 g −1, 2.06 wt% at 77 K and 1 bar), C2 H2 (187.0 cm 3 g −1 at 273 K and 1 bar), and C3 H6 /C3 H8 adsorption capacity (276.5 cm 3 g −1 and 250.4 cm 3 g −1 for C3 H6 and C3 H8 at 273 K and 1 bar), and shows potential for the separation of light hydrocarbons (C2 H2, C2 H4, C2 H6, C3 H6, C3 H8, n -C4 H10, and i-C4 H10 relative to CH4 ), as shown by single component gas sorption and selectivity calculations.